Peculiarities of wheat seed resonant exposure to microwave radiation through oxygen-enriched water - Kovalenko, O.; Kivva, F.; Roenko, A. (Radiofizika i èlektronika, 2021)
Subject and Purpose. Peculiarities are considered of a purposeful modification of the functional indices of wheat seeds upon their soaking in water preliminarily enriched with oxygen and simultaneously irradiated with a low-intensity electromagnetic field (EMF). The aim is to investigate effectiveness of such an indirect exposure of wheat seeds to a low-intensity electromagnetic field related to discrete bands in the extremely high-frequency (EHF) range and depending on the initial state of seeds, “norm” or “pathology”. Methods and methodology. The study comprises experimentally approved radio-physical, radio-engineering and chemical methods. Generators G4-141 (37.5…53.57 GHz) and G4-142 (53.57…78.33 GHz) serve as radiation sources. Oxygen is obtained by reacting a hydrogen peroxide solution with potassium permanganate. The oxygen enrichment of water is executed during its irradiation. The verification of indirect electromagnetic field exposure is based on changes demonstrated by such functional indices of seeds as germination energy and mean lengths of roots and seedlings in each sample. Results. A possibility has been established to modify the functional indices of wheat seeds through their soaking in water preliminarily irradiated with an EMF and simultaneously enriched with oxygen. It has been revealed that the efficiency of the effect depends on whether the seeds are in “normal” or “pathological” state and that a feasibility exists of recovering properties lost in a “pathology” state. The role that the oxygen in the water imbibing the seeds plays in the germination process has been demonstrated. Peculiarities as to the efficiency of wheat seed EMF exposure through the oxygen-enriched water have been shown depending on the signal frequency and length of exposure and on the total energy load. Conclusion. It has been found that substances, including living entities, can be electromagnetically exposed through water. The water-dissipative model of substance exposure to the electromagnetic field has been validated. In this model, water is one of the targets liable to changing its properties at the EMF exposure. This point has been indirectly confirmed by the studies of the states of seeds upon their soaking in the pre-irradiated water. The gas model of the EMF interaction with a substance has been verified, too. A possibility of oxygen activation at resonance irradiation has been shown.